Translation in the Teaching of a Foreign Language As a Means and As an End - Suparmin Suparmin (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
In the history of foreign language teaching translation has alternately been praised and condemned. Unfortunately, the praise and condemnation were based on a rather simplistic, biased, and extreme view of the role of translation. In this view no clear, explicit distinction was made between translation as a means and as an end although in practice people already showed a tendency to be more concerned with one aspect than the other. Moreover, in their treatment of translation people tended to take an Ã¢â¬Åeither Ã¢â¬Â¦ or Ã¢â¬Â¦Ã¢â¬Â position. Either take it or leave it. This paper proposes a more explicit, balanced, and moderate attitude towards translation and its two aspects. It is suggested that a clear distinction be made between translation as a means and as an end and that each be treated accordingly in a better programmed way. The treatment should consider the level of instruction. At the beginning level translation should be treated more as a means than as an end. Gradually, as the level of instruction progresses the role of translation as a means is reduced, while its role as an end is increased so that at the more advanced levels translation will be treated more as an end than as a means. Accordingly, translation should not be totally abandoned or too liberally used. However, the use and disuse should be based on a careful and well-prepared program. In line with the idea that translation be treated as an end at the more advanced level, and considering its importance for a developing nation, it is also proposed here that translating be adopted as a Ã¢â¬Åfifth skillÃ¢â¬Â to be pursued.